A feasibility study of using virtual reality as a pre-occupancy evaluation tool for the elderly - Tseng, Kevin C.; Giau, Do Thi Ngoc (Automation in construction, 2022)
This research aims to investigate the potential adoption of virtual reality (VR) as a pre-occupancy evaluation (PreOE) tool applied for older people, focusing on technology adoption and spatial cognition. An experimental study was conducted to explore simulator sickness, presence, and spatial cognition in immersive VR and non-immersive VR conditions. Thirty-two healthy older participants aged 60 and over were randomly divided equally into two groups, immersive VR and Non-immersive VR. The results indicated that immersive VR is promising to be applied safely for older people with no considerable recorded symptom of simulation sickness (SS). The presentation using immersive VR also provided a higher sense of presence and more accurate spatial cognition. Interestingly, the qualitative data shows positive aspects from the subjects' viewpoint. To conclude, immersive VR is feasible and effective to be used in coupling with conventional methods for the PreOE purpose among older people. •Investigating the potential adoption of virtual reality as a pre-occupancy evaluation tool applied for older people.•Experimenting to explore simulator sickness, presence, and spatial cognition in immersive VR and non-immersive VR environments.•Exploring the safety issues of using the VR tool for older people.